2023
DOI: 10.20944/preprints202307.2008.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Study of the Ecological and Reclamation Condition of Abandoned Lands and their Development for Sustainable Development Goals

Abstract: To provide the population with food, it is very important to re-cultivate "abandoned lands" that have been retired from agricultural use. Conversion of arable land into agricultural abandoned lands in the south of Kazakhstan is, first of all, was primarily associated with salinity. For the purposes of sustainable development, there is a need to develop proposals for re-mastering by studying their current state, reviewing world studies on the reclamation of salt-affected soils. Therefore, this… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…Literature review (Bishimbayeva et al, 2008;Petrick et al, 2017;Laiskhanov et al, 2018;Savelyev, 2018;Mukhamedova and Pomfret, 2019;Kalybekova et al, 2023;Laiskhanov et al, 2023) has shown that to obtain commercially acceptable yields of cotton and alfalfa on grey soils of the Kyzylkum irrigation massif in South Kazakhstan, an integrated approach is required, including crops with high biopotential, agrotechnical practices, reclamation methods and technologies that increase soil productivity and water consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Literature review (Bishimbayeva et al, 2008;Petrick et al, 2017;Laiskhanov et al, 2018;Savelyev, 2018;Mukhamedova and Pomfret, 2019;Kalybekova et al, 2023;Laiskhanov et al, 2023) has shown that to obtain commercially acceptable yields of cotton and alfalfa on grey soils of the Kyzylkum irrigation massif in South Kazakhstan, an integrated approach is required, including crops with high biopotential, agrotechnical practices, reclamation methods and technologies that increase soil productivity and water consumption.…”
Section: Introductionmentioning
confidence: 99%